The Sublime as Continuity System in Islamic Architecture -Mashhad Architecture as a Model- - Mohammed, Nasma Maan; Ali, Rasha AbdUlKarim (Basrah Journal for Engineering Sciences, 2012)
Sublime is considered one of the significant concepts in the recent architectural thought; it has emerged clearly as a mean of creating the highest levels of continuity in architecture, especially in contemporary architectural movements. The importance of sublime especially has emerged. Many architectural studies dealt with concept of sublime in architecture is different and various ways according to the trend of each study; this shows the importance of studying the concept of sublime in the architectural field in general. This study tries to focus on the utilization of the sublime as heritage continuity system in Islamic Architecture because it’s important in the generation of sublimity of architectural models. The paper discusses the importance of this concept and its utilization in the designs, in order to explore the particular problem which has been represented as (The absence of a specific imagination of methods and strategies for achieving sublimation).Thus the objectives of the paper has been formed by building a theoretical framework consisting of two main items of detailed theoretical field which specifies sublime as a concept ,Firstly, Then the application of the important Islamic Architectural products in Mashhad Architecture as a model, Secondly, Finally, concluding utilization of sublime as dogmatically system in Mashhad Architecture, Thirdly, after discussing the results to formulate the conclusions in the end.